2015
DOI: 10.1590/s1984-29612015061
|View full text |Cite
|
Sign up to set email alerts
|

New records of three species of nematodes in Cerdocyon thous from the Brazilian Pantanal wetlands

Abstract: We report the occurrence of nematodes collected from the gut of roadkilled crab-eating foxes (two adult males and one juvenile female), Cerdocyon thous (Linnaeus, 1766), found on the BR 262 highway in Mato Grosso do Sul state, Brazil in 2011. Three helminth species were identified: Ancylostoma buckleyi, Pterygodermatites (Multipectines) pluripectinata, and Ascaridia galli. These nematodes are reported for the first time to infect C. thous from the Brazilian Pantanal wetlands, thereby expanding their geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…Gomes e Vicente (1984) determinaram a presença de enteroparasitos em 71 Nectomys squamipes necropsiados em Sumidouro (RJ), tendo encontrado parasitos em 49 (59,15%) dos animais examinados, encontrando Trematoda (Pseudochinostomum caballeroi), Cestoda (Raillietina sp) e Nematoda (Hassalstrongylus épsilon, Syphacia venteli, Aspidodera raillieti, Physaloptera bispiculata e Litomosoides carinii). Quanto a Cerradomys, o trabalho de Barreto et al (2015) não registra a presença de helmintos, mas apenas de Isospora em um (11,1%) de nove roedores examinados. Em Metachirus já foram descritos o parasitismo por Aspidodera subulata (ARAÚJO, 2011).…”
Section: Resultados E/ou Discussão (Ou Análise E Discussão Dos Resultados)unclassified
“…Gomes e Vicente (1984) determinaram a presença de enteroparasitos em 71 Nectomys squamipes necropsiados em Sumidouro (RJ), tendo encontrado parasitos em 49 (59,15%) dos animais examinados, encontrando Trematoda (Pseudochinostomum caballeroi), Cestoda (Raillietina sp) e Nematoda (Hassalstrongylus épsilon, Syphacia venteli, Aspidodera raillieti, Physaloptera bispiculata e Litomosoides carinii). Quanto a Cerradomys, o trabalho de Barreto et al (2015) não registra a presença de helmintos, mas apenas de Isospora em um (11,1%) de nove roedores examinados. Em Metachirus já foram descritos o parasitismo por Aspidodera subulata (ARAÚJO, 2011).…”
Section: Resultados E/ou Discussão (Ou Análise E Discussão Dos Resultados)unclassified
“…The specimens of Angiostrongylus sp. were posteriorly sequenced according to the methodology described in Gomes et al (2015), and deposited in the GenBank (number MK841610). The sequence indicated that those specimens are neither A. costaricensis, A.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, according to the checklist of helminth parasites in wild carnivore mammals from Brazil (Vieira, Luque, & Muniz-Pereira, 2008), 21 species of hosts are reported for a total of 95 helminth species. After the study of Vieira et al (2008) some new records of helminths in this group of hosts were reported (see Filoni et al, 2009;Gallas & Silveira, 2011;Gallas, Silveira, & Périco, 2014;Gomes, Olifiers, Santos, Simões, & Maldonado, 2015;Gomes, Olifiers, Souza, et al, 2015;Lux-Hoppe, Araújo-de Lima, Tebaldi, & Nascimento, 2010;Pinto, Knoff, Gonçalves, Sanches, & Noronha, 2009;Ribeiro, Verocai, & Tavares, 2009;Suárez, Pesenti, Macedo, Mascarenhas, & Müller, 2015;Vieira et al, 2013). This demonstrates the potential for discovery of new data on the helminth parasites in wild carnivore mammals in Brazil.…”
Section: Introductionmentioning
confidence: 88%